TEACHERS’ PERCEPTIONS ON IMPLEMENTING ESTAFET WRITING TECHNIQUE IN TEACHING WRITING - Saragih, Enni Erawati; Rabbani, Anggi Nur Fitri (ENGLISH JOURNAL, 2017)
Writing is a mental process which needs various technique to teach the students. It seems difficult for students to organize their writing without making a good planning before writing. Many students cannot express their idea because the teacher does not teach them properly. Teaching writing monotonously become a problem for the students to gain the information given by the teacher while learning writing. This research focuses on a technique that is used by teacher in teaching writing; it is called Estafet writing. Detail information about teacher perception on using Estafet writing was described in this research. Descriptive qualitative was used as the research method; interview and questionnaire were used as the instrument for collecting the data. Based on the data, it concludes that teachers’ perception on implementing Estafet Writing technique were positive. The teachers have a good perception on the technique. It proved by the result 90,91% both of teachers agree toward the implementation of Estafet Writing in classroom and 95% they agree toward the effect of student’s ability on implementing the technique. It because the teacher perceived that Estafet Writing is an active learning activity and innovative learning model. The teachers perceived that Estafet Writing is one of a good technique implemented in the classroom because it could be applied easily. Moreover, the learning process was not difficult but choosing the material which is suitable for students was difficult for teachers.